SUSTAINABLE DEVELOPMENT GOALS, HERDING, AND RISK-AVERSE BEHAVIOR IN MUSLIM COUNTRIES - Ooi Kok Loang (Journal of Islamic Monetary Economics and Finance, 2023)
This study examines the impact of Sustainable Development Goals (SDGs) on behavioral biases, namely herding and risk-averse behaviors, in Sharia-compliant stocks. It also explores the mediating effect of investors' sentiments on the relationship between SDGs and behavioral biases. Adopting panel data and quantile regressions, we find that SDGs 4, 8, 10, 11, and 13 significantly and positively correlate with stock returns in Indonesia, Kuwait, Oman, and Qatar. However, SDG 7 is the only SDG goal that is significant to Saudi and UAE stock returns. The results imply a complete mediation as the SDGs have caused changes in investors' sentiment and subsequently triggered the investors to herd and become risk-averse. The impact of SDGs is more pronounced in the upper and lower quantiles of Indonesia, Saudi, and UAE stock returns, as well as the median quantile of Bahrain, Kuwait, Oman, and Qatar stock returns. The results of this study can benefit policymakers, regulators, and practitioners in identifying the best SDG practices to assist Sharia-compliant stocks in Indonesia and Gulf Cooperation Council (GCC) countries to attain better stock returns and improve investors' sentiments and behaviors. The results can also assist governments in weighing the impact and benefits of adopting SDGs in different Muslim countries.